2019
DOI: 10.1093/ejcts/ezz270
|View full text |Cite
|
Sign up to set email alerts
|

The role of primary surgical repair technique on late outcomes of Tetralogy of Fallot: a multicentre study

Abstract: OBJECTIVES Repair of Tetralogy of Fallot (TOF) has currently excellent results with either transventricular or transatrial approach. However, it is unclear as to which has better late outcomes and what role of residual pulmonary valve (PV) regurgitation in the long term is. We report on late clinical outcomes after repair in a large series of patients with TOF, focusing on the type of surgical technique. METHODS This analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…In this cohort, 130 (45.4%) patients underwent repair without TAP augmentation, which is similar to or even better than the results reported by other centers ( 18 20 ). However, it is thought that the placement of the TAP often results in relatively delayed postoperative recovery after surgical repair ( 17 ).…”
Section: Discussionsupporting
confidence: 88%
“…In this cohort, 130 (45.4%) patients underwent repair without TAP augmentation, which is similar to or even better than the results reported by other centers ( 18 20 ). However, it is thought that the placement of the TAP often results in relatively delayed postoperative recovery after surgical repair ( 17 ).…”
Section: Discussionsupporting
confidence: 88%
“…Long-term survival after tetralogy of Fallot (TOF) repair is excellent with almost 95% of patients alive after 25 years [1], and it is mainly determined by the extent of chronic right ventricular (RV) adaptation to the post-surgical right ventricular outflow tract (RVOT) sequelae [2]. Chronic pulmonary valve (PV) regurgitation leads to RV volume overload and subsequent RV remodeling and dysfunction, associated with gradual exercise intolerance, risk of developing rhythm disturbances, and sudden death [3].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of young adults conducted by Ducas et al in Canada, it was found that patients who received TAP surgery had a significantly higher incidence of right ventricular dilation and dysfunction and the need for reintervention at follow-up (most often pulmonary valve replacement) in long term (9) . Similarly, long-term postoperative complications, adverse events, and mortality rates were significantly higher in patients with TAP compared to patients with preserved pulmonary valve in a large multicenter study conducted by Padalino et al our study included patients who received PVSS (10) . In considering the total number of patients who underwent complete corrective repair (TAP: n= 33, PVSS: n= 30, total correction with conduit: n= 11), the PVSS rate was 40.5%, slightly higher than the results of the mentioned Italian study (10) .…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, long-term postoperative complications, adverse events, and mortality rates were significantly higher in patients with TAP compared to patients with preserved pulmonary valve in a large multicenter study conducted by Padalino et al our study included patients who received PVSS (10) . In considering the total number of patients who underwent complete corrective repair (TAP: n= 33, PVSS: n= 30, total correction with conduit: n= 11), the PVSS rate was 40.5%, slightly higher than the results of the mentioned Italian study (10) . With this result, it has been evaluated that advanced international standards have been achieved in our center.…”
Section: Discussionmentioning
confidence: 91%